Sifat tanda pembelajaran bahasa ke arah keusahawanan. - Dani, Noor Aina; Abdullah, Faiz Sathi (2012)
It is assumed that language learning can be channeled for knowledge benefit and the ability to live outside the university environment. that is, community.For that purpose, the process of language learning needs to be congruent with the stability of internal factors (disposition) and external factors (situational). This stability generates language learning achievements needed by students, with the lecturer as facilitator. In this research, it was found that the attribution of language learning which develops entrepreneur attitudes supports the stability of external elements, especially in language learning situations in tandem with course selection, academic staff, transfer of knowledge, and workplace values.